Sociological Analysis of Local Support Practices Contribute into Strengthening Entrepreneurs Capacity - Adhikari, Shukra Raj; Chongbang, Nirmal; Bhandari, Manoj (Intellectual Journal of Academic Research, 2024)
Local support practices and community-based supporting systems are the socio-cultural initiatives. This paper aims to explore how social support practices contributed to the sustainability of local enterprises during the local crises, a period marked by weak informal support systems, inadequate risk transfer measures, and insufficient state recovery policies and budgets. To gain the objective both qualitative and quantitative data has been collected under the qual-quan research design. The research area has been located in Kaski, Tanahu and Gorkha district. Using convenience sampling of thirty-six micro and small entrepreneurs across Kaski, Tanahu, and Gorkha districts in Nepal. The research employed case study method, observation and closed-ended questionnaires methods to gathered the data. The findings indicate that while local self-saving efforts and community support significantly strengthened resilience among entrepreneurs, informal support practices and state support policies need to be reshaped. The study concludes that enhancing both local support mechanisms and state engagement is essential for improving entrepreneurial sustainability in future crises.